Velocity-map imaging study of the photodissociation of acetaldehyde. - Cruse, H; Softley, T (2005)
Velocity-map imaging studies are reported for the photodissociation of acetaldehyde over a range of photolysis wavelengths (317.5-282.5 nm). Images are obtained for both the HCO and CH3 fragments. The mean rotational energy of both fragments increases with photodissociation energy, with a lesser degree of excitation in the CH3 fragment. The CH3 images demonstrate that the CH3 fragments are rotationally aligned with respect to the recoil direction and this is interpreted, and well modeled, on the basis of a propensity for forming CH3 fragments with M approximately K, where M is the projection of the rotational angular momentum along the recoil direction. The origin of the CH3 rotation is conserved motion from the torsional and methyl-rocking modes of the parent molecule. Nonstatistical vibrational distributions for the CH3 fragment are obtained at higher energies.